Comportamento hidrológico de pequenas bacias hidrográficas com três espécies de Eucalyptus no bioma Pampa - Ferreto, Décio Oscar Cardoso (2019)
The establishment of Eucalyptus plantation in areas previously used for agriculture and livestock in the Pampa biome has generated questions about possible negative environmental impacts, mainly related to water consumption by that culture. However, mostly of these questions need scientific basis. This study investigated the influence of the land cover on the hydrological behavior of small paired watersheds: two watersheds with Eucalyptus plantation, one with Eucalyptus saligna (plants between 7.5 and 11.5 years of age; EsW) and another with E. benthamii (plants between 0.5 and 4.5 years of age; EbW), and a third watershed under degraded grassland (GW), used for livestock production. The components of the hydrological cycle of three watersheds located in São Gabriel-RS were monitored for four years from October 2014 to September 2018. The variables monitored were: rainfall (Pt), streamflow (Q), water storage variations in the soil profile, Throughfall, Stemflow, litter interception, total height and diameter at 1.30 meters high of the trees. Also, were estimated, actual evapotranspiration, canopy interception (INT), leaf area index, water deficit, water surplus and withdrawal and put backr into the soil profile. It was also analyzed the diferences in the partitioning of the rainfall in three young eucalyptus species (E. saligna, E. benthamii and E. dunni, 2 at 4.5 years). Besides that, the manejement of shallow cutting of 100% and 30% in the eucalyptus watersheds. There were three years with precipitation far above the historical average in the region during the study. It was observed a lower Q of the EsW in relation to GW of 44.9, 44.5, 55.7 and 58.2%, from hydrological year 1 to 4, respectively, and a reduction in BEb in relation to GW of 16.4, 36.2, 66.5 and 78.4% of the year hydrological 1 to 4, respectively. The main water outlet in the three BHs occurred by the ETa process. The largest water deficits, during the four hydrological years of the study, occurred in BEs and BEb and the highest water surplus were estimated for BC. The specific flow rate (L s-1 km-2), before the cut of 100% of the area with eucalyptus in the EbW represented 5.4% of Pt and after the cut represent 23.7% of Pt. The highest averages of INT were verified in the species E. saligna and E. dunnii, when the plants had 3 to 4 years of age. The lower averages of INT, during all study period occurred in the E. benthamii species. In periods with low rainfall the BEs provided more water downstream than the BC in 65% of the time. The mosaic management of ages, by means of cutting in 30% of the eucalyptus area in the BEs, was beneficial for the maintenance of the minimum streamflow.